Irony and Satire in the Very Short Story - ouledbrahim, asma; bouchefra, nadia (El Omda in Linguistics and Discourse Analysis, 2023)
One of the most important characteristics and aesthetics of the very short story, paradox and irony, where the power of the very short story lies in its speed and its terrible ability to reach the desired goal in moments, as far as it adopts in the inclusion and deletion, strives to breach the horizon of waiting for the reader and amaze him by playing on the paradox and irony that is often used to monitor social phenomena striped and expose their disadvantages.